Oltre il topos letterario: il locus amoenus come spazio vissuto nei dialoghi ciceroniani - Beyond the Literary Topos: the Locus Amoenus as Inhabited Space in Cicero's Dialogues - Valentina Calcò (Ciceroniana On Line)
This paper seeks to examine the existential significance of the description of place in Cicero’s works. Descriptions of the locations in which philosophical dialogues are set serve more than an ornamental function, adding an essential element to the discourse. The presence of loci amoeni in the dialogues’ frames constitutes a generic sphragis for the philosophical dialogue, as these loci are imbued with an atmosphere that identifies them as lived spaces. In view of the lack of ancient perspectives on the perception of space, my reading draws on recent phenomenological theories to investigate this theme. The possibility of deploying this modern lens to interpret the ancient material is granted by the transhistorical nature of the object of our study, as characterised in the phenomenological literature: place is not a cultural product, subject to the change, but something universal that concerns an essential aspect of human life.